Semiotic Study and the Value of Islam in Oral Tradition of Sariga in Muna Society of South Sulawesi Province - Saidiman; Sumiyadi; Iskandar Wassid; Tedi Parmadi (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2020)
This study examines semiotic study and the value of islam in oral tradition of Sariga in Muna society of south Sulawesi Province.??. Semiotic meaning and islamic values ??in the Muna community are widely applied through local traditions in the community and one of them is the oral tradition of Sariga. The problem in this study is